Effect of molar concentration on the structural, linear and nonlinear optical properties of CuS (covellite) thin films. (1st September 2022) - Habiboglu, C.; Erken, O.; Gunes, M.; Yilmaz, O.; Cevlik, H.C.; Ulutas, C.; Gumus, C.
Abstract: CuS thin films with various molar concentrations at 70 °C temperature were deposited by Chemical Bath Deposition. The effect of molar concentration on the structural, linear optic, nonlinear optic and morphological properties of CuS films were deeply investigated. X-ray diffraction (XRD) analysis exhibited that CuS films were formed in polycrystal structure and hexagonal phase. The fundamental optical parameters of films such as energy band gap, reflection and extinction coefficient were determined with the results of optical transmission and optical absorption by UV–vis spectrophotometer. The energy band gap values were reduced with increasing films thickness. Moreover, the dependence of the optical dielectric constants, loss tangent, optical conductivity, surface and volume energy loss function values on the molar concentrations were studied. Furthermore, the third order nonlinear optical susceptibility and nonlinear refractive index, which is considered to be the base of the first order optical susceptibility with nonlinear optical properties were discussed in detail. Highlights: Copper sulfide (CuS, covellite) thin films were prepared at various molar concentrations (0.1 M, 0.3 M, 0.5 M) at a temperature of 70 °C by Chemical Bath Deposition. The energy band gap reduced with increasing the thickness of CuS thin films. The refractive indices of the films obtained at 0.1 M, 0.3 M and 0.5 M at 550 nm were calculated as 2.31, 2.63 and 2.64, respectively. It was determined that the first-order optical susceptibility values of CuS films varied in the range of 0.268–3.031 in the visible region. The third-order nonlinear optical susceptibility values varied in the range of 8.75 × 10 −10 –1.44 × 10 −5  esu.